University-business-government collaboration: from institutes to platforms and ecosystems - Göte S. Nyman (Triple Helix, 2015)
An outline for a platform-based, bottom-up model, based on extensive project practices, is introduced for the university-business-government collaboration (UXC) analysis. Current internal incentive problems of UXC at universities especially in Europe are considered and guidelines introduced for a fast-lane platform model for building agile UXC knowledge engines. Experiences and learning lessons from small-scale, university-business-government collaboration cases are described and used as supporting knowledge for the hypothetical, bottom-up type of collaboration model. The practice experiences emphasize the role of the individual actors in opportunity pursuit and the value of the traditional academic capabilities as self-organizing elements in a successful UXC.
Keywords: 330; Triple Helix; University; Business; Collaboration; Platform